1998
DOI: 10.1073/pnas.95.25.15123
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate binding and resistance to proteolysis control insecticidal activity of Griffonia simplicifolia lectin II

Abstract: Griffonia simplicifolia leaf lectin II (GSII), a plant defense protein against certain insects, consists of an N-acetylglucosamine (GlcNAc)-binding large subunit with a small subunit having sequence homology to class III chitinases. Much of the insecticidal activity of GSII is attributable to the large lectin subunit, because bacterially expressed recombinant large subunit (rGSII) inhibited growth and development of the cowpea bruchid, Callosobruchus maculatus (F). Site-specific mutations were introduced into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 40 publications
0
81
0
5
Order By: Relevance
“…Additional support for such a mode of action comes from the observation that for the Griffonia simplicifolia lectin (GS-II) there is a clear correlation between receptor binding and toxicity towards the cowpea bruchid Callosobruchus maculatus (Zhu-Salzman et al, 1998). In addition, lectins may also act as a feeding deterrent leading to reduce food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for such a mode of action comes from the observation that for the Griffonia simplicifolia lectin (GS-II) there is a clear correlation between receptor binding and toxicity towards the cowpea bruchid Callosobruchus maculatus (Zhu-Salzman et al, 1998). In addition, lectins may also act as a feeding deterrent leading to reduce food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms of insecticidal action of lectins remain unknown, though it has been suggested that this entomotoxic activity seems to depend upon the carbohydrate recognition property they exhibit. Plant lectins with affinity for N-acetylglucosamine and chitin-binding property are able to bind chitin and glycosylated proteins of the peritrophic matrix, interfering in the digestion and absorption of nutrients (Tellam et al, 1999;Peumans and Van Damme, 1995;Zhu-Salzman et al, 1998;Zhu-Salzman and Salzman, 2001;Carlini and Grossi-de-Sá, 2002;Macedo et al, 2004;Macedo et al, 2007). The peritrophic matrix constitutes a membrane found in the midgut that separates the contents of the gut lumen from the digestive epithelial cells.…”
Section: Insecticidal Activity Of Lectinsmentioning
confidence: 99%
“…Lectins have deleterious effects against larvae, developing stages and mature forms of insects from orders Coleoptera, Diptera, Hemiptera, Homoptera, Hymenoptera, Isoptera, Lepidoptera and Neuroptera (Murdock et al, 1990;Eisemann et al, 1994;Powell et al, 1995;Zhu-Salzman et al, 1998;Bandyopadhyay et al, 2001;Isidro et al, 2001;Hogervorst et al, 2006;Kaur et al, 2006;Coelho et al, 2007;Macedo et al, 2007;Fitches et al, 2008;Sá et al, 2008;Coelho et al, 2009;Sá et al, 2009c;Silva et al, 2009;Napoleão et al, 2011;Souza et al, 2011b). Insecticide activity of lectin is generally evaluated by bioassays that incorporate the lectin into artificial diets offered to insects, with insects dying from nutritional deprivation.…”
Section: Insecticidal Activity Of Lectinsmentioning
confidence: 99%
“…If a lectin is resistant to proteolytic digestion by the insect, it can also bind to the insect gut. Hence, resistance to proteolysis is another aspect of the toxicity of a lectin, as shown by Zhu-Salzman et al (1998), Zhu-Salzman and Salzman (2001), and Lagarda-Diaz et al (2009). Foissac et al (2000 indicate that the binding of a lectin is not the only parameter for its toxicity level.…”
Section: Specific Binding Is Needed For a Lectin To Have An Effectmentioning
confidence: 99%